Analisis Pengaruh Pertumbuhan Ekonomi Terhadap Kemiskinan melalui Kualitas Pembangunan Manusia sebagai Variabel Intervening di Kabupaten Nabire - Irwan Dwi Saputra; Agustina Sanggrangbano (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2025)
This study aims to analyze the effect of economic growth on poverty in Nabire Regency with the quality of human development measured by the Human Development Index (HDI) as an intervening variable. Using a quantitative approach with secondary data from the Central Bureau of Statistics (BPS) for the period 2010 to 2023, the analytical methods employed are multiple regression analysis, path analysis, and the Sobel test to examine the significance of HDI's mediating role. The results show that GRP has a positive and significant effect on HDI (0.967), GRP has a negative and significant direct effect on poverty (-0.853), and HDI has a negative and significant effect on poverty (-0.783). The Sobel test proves that HDI acts as a significant intervening variable with a test statistic value of -4.133 and a p-value of 0.000. The indirect effect of GRP on poverty through HDI reaches -0.757, making the total effect of GRP on poverty -1.610. This means that nearly half (approximately 47 percent) of the total effect of economic growth on poverty reduction is channeled through improvements in the quality of human development. Keywords: Economic Growth, Poverty, Quality of Human Development, Path Analysis